Accelerating Biphasic Biocatalysis through New Process Windows. Issue 38 (14th July 2020) - Huynh, Florence; Tailby, Matthew; Finniear, Aled; Stephens, Kevin; Allemann, Rudolf K.; Wirth, Thomas
Abstract: Process intensification through continuous flow reactions has increased the production rates of fine chemicals and pharmaceuticals. Catalytic reactions are accelerated through an unconventional and unprecedented use of a high‐performance liquid/liquid counter current chromatography system. Product generation is significantly faster than in traditional batch reactors or in segmented flow systems, which is exemplified through stereoselective phase‐transfer catalyzed reactions. This methodology also enables the intensification of biocatalysis as demonstrated in high yield esterifications and in the sesquiterpene cyclase‐catalyzed synthesis of sesquiterpenes from farnesyl diphosphate as high‐value natural products with applications in medicine, agriculture and the fragrance industry. Product release in sesquiterpene synthases is rate limiting due to the hydrophobic nature of sesquiterpenes, but a biphasic system exposed to centrifugal forces allows for highly efficient reactions. Abstract : A new application of high‐performance liquid/liquid counter current chromatography system demonstrated high reaction rates and excellent yields for biphasic reactions, exemplified with steroselective phase‐transfer catalysed reactions and biocatalytic synthesis of sesquiterpenes. Catalysis in the HPCCC system was up to 70 times faster than in batch reactors and up to 10 times faster than in segmented flow systems with nearly quantitative yields.